1998
DOI: 10.1084/jem.187.8.1205
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Membrane-bound Fas(CD95) Ligand to Its Soluble Form Is Associated with Downregulation of Its Proapoptotic Activity and Loss of Liver Toxicity

Abstract: Human Fas ligand (L) (CD95L) and tumor necrosis factor (TNF)-α undergo metalloproteinase-mediated proteolytic processing in their extracellular domains resulting in the release of soluble trimeric ligands (soluble [s]FasL, sTNF-α) which, in the case of sFasL, is thought to be implicated in diseases such as hepatitis and AIDS. Here we show that the processing of sFasL occurs between Ser126 and Leu127. The apoptotic-inducing capacity of naturally processed sFasL was reduced by >1,000-fold compared with membrane-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
594
6
4

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 742 publications
(629 citation statements)
references
References 55 publications
25
594
6
4
Order By: Relevance
“…The 39-40 kDa band corresponds to the described MW of the unprocessed, microvesicle-bound form of CD95L. 52,56 (d) Purified unstimulated primary CD4 þ T cells (10 6 /ml) were incubated with viruses (500 ng p24/ml) purified from living HeLa cells transfected with NL4-3 or with NL4-3/Denv, and with either supernatants from the Neuro-2a FasL cell line (Neuro-2a FasL), which contain microvesicle-bound, unprocessed CD95L, 57 51,[53][54][55] Western blot analysis of the purified supernatants of living or dying (serum deprived) control HeLa cells, using a CD95L-specific antibody, showed the presence of a 39-40 kDa CD95L in the latter (as in the positive control Jurkat cell cytoplasmic lysates) and no detectable CD95L in the former (Figure 5c). To further investigate the potential role of CD95L, we incubated CD4 þ T cells with supernatants from the Neuro-2a FasL cell line, which contain microvesicle-bound, unprocessed CD95L released by these cells.…”
Section: Cd95l Released By Dying Cells Is One Of the Cellular Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 39-40 kDa band corresponds to the described MW of the unprocessed, microvesicle-bound form of CD95L. 52,56 (d) Purified unstimulated primary CD4 þ T cells (10 6 /ml) were incubated with viruses (500 ng p24/ml) purified from living HeLa cells transfected with NL4-3 or with NL4-3/Denv, and with either supernatants from the Neuro-2a FasL cell line (Neuro-2a FasL), which contain microvesicle-bound, unprocessed CD95L, 57 51,[53][54][55] Western blot analysis of the purified supernatants of living or dying (serum deprived) control HeLa cells, using a CD95L-specific antibody, showed the presence of a 39-40 kDa CD95L in the latter (as in the positive control Jurkat cell cytoplasmic lysates) and no detectable CD95L in the former (Figure 5c). To further investigate the potential role of CD95L, we incubated CD4 þ T cells with supernatants from the Neuro-2a FasL cell line, which contain microvesicle-bound, unprocessed CD95L released by these cells.…”
Section: Cd95l Released By Dying Cells Is One Of the Cellular Factorsmentioning
confidence: 99%
“…The microvesicle-bound, unprocessed form of CD95L has a higher aggregation degree, and hence death signaling efficiency, than its soluble 26 kDa form. 54 However, a similar aggregation degree can be achieved by crosslinking soluble recombinant (sr) FLAG-tagged CD95L, using FLAG-specific antibodies. 54 We incubated CD4 þ T cells with either FLAG-specific antibody-crosslinked soluble recombinant FLAG-tagged CD95L (srCD95L), noncrosslinked srCD95L, or the FLAGspecific antibody alone, in the presence of either NL4-3 or NL4-3/Denv viruses purified from living transfected HeLa cells.…”
Section: Cd95l Released By Dying Cells Is One Of the Cellular Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…sFasL can either cause apoptosis at a distant site 6,7 or alternatively dampen the apoptotic response by blocking Fas receptors. 8,9 The fate of the remaining membrane-anchored N-terminal portion of FasL, which comprises a transmembrane region and the proline-rich FasL intracellular domain (FasL ICD), has not been studied so far.…”
mentioning
confidence: 99%
“…Several studies have shown that FasL expression is implicated in HCC and is enhanced in regions with infiltrating inflammatory cells on the margins of the cancerous tissue (18)(19)(20). In vitro studies have revealed that the capacity of naturally processed sFasL to induce apoptosis is less potent than that of cell surface FasL, possibly due to decreased capability to cross-link Fas (21,22). On the other hand, in vivo studies have shown that injection of sFasL can induce tumor cell apoptosis and hepatocyte apoptosis, which cause liver failure (23,24).…”
Section: Introductionmentioning
confidence: 99%